Wisata Petualangan: Menguji Faktor Pendorong Niat Berkunjung Wisatawan Pada Destinasi Wisata - Pohan, Muhammad Yasir Arafat (Jurnal Manajemen Akuntansi (JUMSI), 2024)
Indonesia is a country that has stunning natural beauty, as evidenced by its famous tourist destinations and even become a destination for foreign tourists such as Bali, Lombok, Labuan Bajo, Lake Toba and others. With so many nature-based tourist destinations, of course it is an opportunity to be able to increase local and foreign tourist visits. In order to increase tourist intention to visit, it is necessary to know the driving factors for the emergence of tourist intention to visit. This study aims to examine the factors driving the intention to visit adventure tourists in Indonesia. Intrinsic motivation, destination image and attitude are used as predictors in this study which are then tested for their effect on the intention to visit adventure tourists in Indonesia. This study used a quantitative approach using a questionnaire instrument which was distributed to 150 respondents, the questionnaire was distributed via the Google form link to make it easier to reach many respondents. Data were analyzed using Structural Equation Modeling-PLS. The test results show that intrinsic motivation, destination image, attitudes, subjective norms have a positive and significant influence on the intention to visit adventure tourists in Indonesia.